Variable Switching Point Model-Free Predictive Current Control Strategy for SRM - Han, Guoqiang; Zhang, Lin; Wang, Yige; Xu, Shuai; Yu, Dongsheng (IEEE transactions on industrial electronics (1982), 2025)
The control performance of the model predictive current control method is subject to the motor model, and the fixed switching point based strategy has the disadvantage of large current ripple. To avoid the problems, a variable switching point model-free predictive current control (VSP-MFPCC) method for switched reluctance motor (SRM) is proposed. First, the current ultralocal model of SRM is established, and the nonlinear disturbance observation is proposed to estimate the total disturbance of the system. Then the phase current of the next sampling point is predicted without motor model. Second, the variable switching point is identified by calculating the action time of the voltage vector at the present sampling point. The optimal voltage vector will be selected with the designed cost function. The phase current ripple and the robustness of the control strategy will be improved with the proposed VSP-MFPCC method. The effectiveness of the proposed method is validated with simulations and experiments.